Primary aortoduodenal fistula: A case report and review of literature. (2018) - Ishimine, Tohru; Tengan, Toshiho; Yasumoto, Hiroshi; Nakasu, Akio; Mototake, Hidemitsu; Miura, Yuya; Kawasaki, Kyohei; Kato, Takashi
Highlights: Primary aortoduodenal fistula (PADF) is extremely rare. A PADF case was treated by in situ aortic reconstruction and omental coverage. An elderly man with hematemesis was diagnosed with PADF. The patient had uneventful recovery and discharged 86 days after surgery. Abstract: Background: Primary aortoduodenal fistula (PADF) is an abnormal connection between the aorta and the duodenum and is a life-threatening condition. It is a very rare cause of gastrointestinal bleeding, which often leads to delay in its diagnosis. Prompt diagnosis and surgical treatment are crucial to improve the outcome of patients with PADF. Presentation of case: An 82-year-old man with a history of untreated abdominal aortic aneurysm (AAA) presented to the emergency department with hematemesis. Computed tomography (CT) revealed an AAA with air within the thrombus wall and disruption of the fat layer between the AAA and duodenum, indicating PADF. Emergent surgery, in situ aortic reconstruction using a Dacron graft, and omental coverage were performed. Although the patient needed another surgery for postoperative chylous ascites, he made good recovery and was discharged 86 days after initial surgery. Discussion: In our case, the patient presented with hematemesis and a pulsatile abdominal mass on physical examination and had a history of untreated AAA, which helped in prompt diagnosis of PADF. CT findings suggesting PADF include disappearance of the fat plane between the aneurysm and duodenum, air in the retroperitoneum or within the aortic wall, and contrast enhancement within the duodenum. The recommended surgical approach for PADF consists of aortic reconstruction (in situ aortic reconstruction or extra-anatomical bypass) and duodenal repair. Conclusion: Our report affirms that CT and open surgery are effective diagnostic and treatment options, respectively, for PADFs.